Penerapan Proyek Penguatan Profil Pelajar Pancasila Pada Tema Kearifan Lokal Kelas III Di SD Plus Pesantren Al Anwar Pacul Gowang - Astutik, Anik; Rahma Pratiwi, Emy Yunita; Faizi, Ahmad (IJPSE Indonesian Journal of Primary Science Education, 2024)
Since the new teachings of 2022–2023, the Al Anwar Pacul Gowang Islamic Boarding School Plus Elementary School has used the Independent Curriculum. establishing the Pancasila Student Profile as the cornerstone for cultivating pancasila-compatible character values. Its implementation is done through extracurricular and curricular (project-based) activities. The following are the 6 dimensions of Pancasila student profiles:: 1) Faith, Fear of God Almighty and noble character, 2) Global Diversity, 3) Mutual Cooperation, 4) Independent, 5) Critical Reasoning, 6) creative. The results of the study show that (1) The study's findings indicate that (1) Implementation of a project to enhance Pancasila students' profiles on the topic of class III local wisdom, in which the teacher creates materials and programs to be implemented over the course of one semester in order to ensure that the composition is well-designed, and that there are program benefits when students complete projects that are provided. (2) The ability to foster a sense of healing toward cultural variety, create innovative works and acts, and conduct projects to raise the profile of Pancasila class III students are demonstrated through efforts to increase student creativity. Not only that, but personality, emotional character, intellectual, language, cognitive character, and moral development all proceed at a rapid rate alongside physical and motor development. (3) Implementing the project to develop Pancasila student profiles on the topic of local knowledge has run into a number of challenges, including the teacher council's lack of cooperation, a lack of resources and infrastructure, and parental opposition. Increased collaboration with teacher boards and full facilities are the answers to these problems.